Disentangling dyskinesia from parkinsonism in motor structures of patients with schizophrenia. Issue 4 (23rd July 2022) - Sakreida, Katrin; Chiu, Wei-Hua; Dukart, Juergen; Eickhoff, Simon B; Frodl, Thomas; Gaser, Christian; Landgrebe, Michael; Langguth, Berthold; Mirlach, Daniela; Rautu, Ioana-Sabina; Wittmann, Markus; Poeppl, Timm B
Abstract: Patients with schizophrenia frequently suffer from motor abnormalities, but underlying alterations in neuroarchitecture remain unclear. Here, we aimed to disentangle dyskinesia from parkinsonism in motor structures of patients with schizophrenia and to assess associated molecular architecture. We measured grey matter of motor regions and correlated volumetric estimates with dyskinesia and parkinsonism severity. Associations with molecular architecture were identified by cross-modal spatial correlations between ensuing maps of abnormality-related volume alterations and neurotransmitter maps from healthy populations. Both phenomena were linked to (specific) striatal and basal forebrain reductions as well as to D1 receptor density. Dyskinesia also manifested in cerebellar decrease, while parkinsonism was associated with less motor cortex volume. The parkinsonism-related brain pattern was additionally associated with 5-HT1A/2A and µ-opioid receptors distribution. Findings suggest the need to develop psychopharmacological compounds that display not only selectivity for receptor subtypes but also anatomical selectivity for alleviating dyskinesia without worsening parkinsonism and vice versa. Abstract : Sakreida et al . identify common as well as distinct structural brain changes and associated molecular mechanisms linked to dyskinesia and parkinsonism in schizophrenia. Motor abnormality-specific effects suggest the need for psychopharmacological compounds with selectivity for not only receptor subtypes but also anatomy. Graphical Abstract: Graphical abstract